Globalisation and India's Role in the International Trade of Services (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Within the framework of globalization, this article delves at India's participation in the international trade of services. Trade in services has expanded in significance and is now an integral part of the global economy due to the increased connectivity of the globe. In recent years, India's plentiful human resources, technical prowess, and reasonably priced services have propelled the nation to the forefront of the global services industry. India has achieved remarkable success in this field, and this essay delves into the many factors—including education, technology, legislation, and the role of the private sector—that have contributed to this. Next, the issues that India is facing are discussed, including potential trade barriers and the growing rivalry from other emerging economies.